Reviews Summer 2020 - Adriano Marinazzo; Stefaan Vervoort; Matthew Allen; Gregorio Astengo; Julia Smyth-Pinney (Architectural Histories, 2020)
Marinazzo, A. A Review of William E. Wallace, 'Michelangelo, God’s Architect: The Story of His Final Years and Greatest Masterpiece'. Princeton and Oxford: Princeton University Press, 2019. Vervoort, S. A Review of Matthew Mindrup, 'The Architectural Model: Histories of the Miniature and the Prototype, the Exemplar and the Muse'. Cambridge, MA, and London: The MIT Press, 2019. Allen, M. A Review of Joseph Bedford, ed., 'Is There an Object-Oriented Architecture? Engaging Graham Harman'. London and New York: Bloomsbury Academic, 2020. Astengo, G. A Review of Vaughan Hart, 'Christopher Wren: In Search of Eastern Antiquity'. London: Yale University Press, 2020. Smyth-Pinney, J. A Review of Maria Beltramini and Cristina Conti, eds., 'Antonio da Sangallo il Giovane: Architettura e decorazione da Leone X a Paolo III'. Milan: Officina libraria, 2018.